Study on The Effect of Soft Story on Infill RC Frames Under Seismic Effect - Bhatta, Mahesh Raj; Pradhan, Prachand Man; Jha, Sudip (Kathmandu University Journal of Science Engineering and Technology, 2018)
Construction practice of reinforced concrete (RC) frames infilled with unreinforced masonry is quite common now-days in urban cities in Nepal and elsewhere. Previous study shows the lateral load transfer mechanism is different than that of bare frames in infill buildings. Because of the unavoidable circumstances like elimination of central columns, elimination of infill wall in basement for parking purpose and reducing the size of frame members etc. may cause the particular story to be soft.